Google Workspace as a b-learning platform. Analysis of the perceptions of the Degrees in Communication - Inmaculada Martín-Herrera; Juan Pablo Micaletto-Belda; David Polo Serrano (Universidad de Guadalajara, 2021)
This article has investigated the perceptions about the educational use of the Google Workspace (formerly Google Suite) of a group of 131 students who are studying Communication Sciences and Digital Communication degrees at a University Center in the province of Seville, Spain. The main objective of the research was to collect and analyse the educational experience and the competences developed by these students with this software suite in university education. To do so, a descriptive research was designed based on a quantitative and qualitative analysis using an online questionnaire. The results showed that these university students value favourably the interface and services provided by this platform, especially Meet, Documents, Gmail, Classroom and Presentations. However, they perceive that other applications, such as Keep, Jamboard or Tasks, are not very useful. In short, blended learning models proposed by Google Workplace have proven useful in the university field, and that students have adapted adequately to the new learning environment.